Sensing Enhancement of Electromagnetically Induced Transparency Effect in Terahertz Metamaterial by Substrate Etching - Lin, Tingling; Huang, Yi; Zhong, Shuncong; Luo, Manting; Zhong, Yujie; Yu, Yingjie; Ding, Jian (Frontiers in Physics, 2021)
A broad range of terahertz (THz) metamaterials have been developed for refractive index sensing. However, most of these metamaterials barely make sufficient use of the excited electric field which is crucial to achieve high sensitivity. Here, we proposed a metamaterial sensor possessing electromagnetically induced transparency (EIT) resonance that is formed by the interference of dipole and quadrupole resonance. In particular, the strengthening of light-matter interaction is realized through substrate etching, leading to a remarkable improvement in sensitivity. Hence, three kinds of etching mode were presented to maximize the utilization of the electric field, and the corresponding highest sensitivity is enhanced by up to ~2.2-fold, from 0.260 to 0.826 THz/RIU. The proposed idea to etch substrate with a strong light-matter interaction can be extended to other metamaterial sensors and possesses potential applications in integrating metamaterial and microfluid for biosensing.